An experimental investigation of evaporation rates for different volatile organic compounds. Issue 2 (8th February 2013) - Heymes, Frédéric; Aprin, Laurent; Bony, Aurélia; Forestier, Serge; Cirocchi, Stefano; Dusserre, Gilles
<x xml:space="preserve">Abstract</x> Experiments were performed in order to measure evaporation rates of four different volatile organic compounds (VOC; 2‐propanol, 1‐hexene, acetone, propanal) and water. Evaporation mass flow rates and liquid temperatures where recorded. Different correlations were tested versus the experimental. Exponents and constant were recalculated to fit the experimental data. This new correlation was tested on an additional VOC experimentation (ethanol) and the accuracy of the correlation was satisfying. The correlation robustness was investigated versus temperature and wind velocity. © 2013 American Institute of Chemical Engineers Process Saf Prog, 2013